Hyponatremia During Induction Therapy in Distinct Pediatric Oncological Cohorts: A Retrospective Study - Salvador, Christina; Salvador, Robert; Willeit, Peter; Kuntner, Christine; Haid, Alexandra; Müller, Thomas; Kropshofer, Gabriele; Crazzolara, Roman (Frontiers in Oncology, 2021)
Abstract Background: Hyponatremia is a well-known adverse event of repeated therapy with vincristine in oncological patients. But, to date, data in pediatric patients with malignant diseases other than acute lymphoblastic leukemia (ALL) are sparse or lacking. Materials and Methods: A retrospective study of 98 pediatric patients was conducted to analyze the incidence of hyponatremia in a caucasian cohort of newly diagnosed ALL. For comparison we further examined five other pediatric oncological cohorts (Hodgkin’s disease, Ewing sarcoma, Wilms tumor, benign glioma of the CNS, Langerhans cell histiocytosis), that receive alkaloids in their induction regimes. Results: We found a high incidence of hyponatremia (14.7%) in our ALL cohort with a trend towards male patients of elementary school age. None of the affected patients showed neurological symptoms. By comparison, patients from other malignancy groups did not show significant hyponatremia, regardless of their comparable therapy with alkaloids. We here show a noticeable coincidence of hyponatremia and hypertriglyceridemia in ALL patients, indicating a possible role of L-asparaginase related hypertriglyceridemia in the development of severe hyponatremia in such patients. Conclusion: We report a higher incidence of hyponatremia following vincristine therapy in caucasian children with ALL than published before. This hyponatremia could not be demonstrated in other oncologic cohorts treated with alkaloids. L-asparaginase induced hypertriglyceridemia may play a role in the certainly multifactorial development of hyponatremia in childhood leukemia.